The Vatican Palace and the Formation of the Roman Palazzo in the Second Half of the 15th Century - Dunina, Maria V. (Actual Problems of Theory and History of Art, 2016)
In mid. 15th century Rome, which was barely recovering from the devastating period of Avignon Papacy, the private construction was not supported by any theoretical basis or consistent logic of an artistic conception. The situation changed radically when Pope Nicholas V (1447–1455) set a goal to create a new image of the Eternal City. In the historiography of architecture of the 15th century, the Roman palazzo did not receive adequate attention. The creation of secular architecture of the Renaissance is often associated solely with the Florentine tradition, which did not appear in Rome until the end of the 1480s. There was almost no attempt to trace the birth and the development of the Roman palazzo. According to the author, the Vatican wing of Nicholas V established the clear typology of the Roman palazzo, consistent with ideas of  L. B. Alberti. The earlier palaces — St. Apollinare, Capranica, Orsini — present a chaotic combinations of vertical and horizontal articulation, living apartments, towers and loggias. In Vatican palace and the palaces built after its example, the same elements are arranged as a homogeneous monumental structure. The author highlights the following steps in the development of the Vatican palace type: 1) the emergence of huge courts that repeat the motifs of the Loggia of the Blessings; (Palazzo Venezia and Palazzo Borgia); 2) an increase in the number of references to antiquity (Palazzo Nardini, della Rovere, San Pietro in Vincoli, Santi Apostoli); 3) the Roman palace all’antica (the role of angular towers and the Vatican planning system in the construction of Palazzo Cancelleria and Castellesi).
Keywords: Italian Renaissance; quattrocento; palazzo; Early Renaissance architecture; Rome; Vatican palace; Leon Battista Alberti; Pope Nicolas V